Role of polysaccharides in tribological and sensory properties of model dairy beverages. (January 2023) - Ji, Lei; Otter, Denise den; Cornacchia, Leonardo; Sala, Guido; Scholten, Elke
Abstract: In this study, we investigated the contribution of different polysaccharides that varied in conformation and molecular weight, i.e. maltodextrin, xanthan gum, guar gum, carboxymethyl cellulose, and maize starch, to the frictional and sensorial properties of model dairy-based beverage systems, containing 5% emulsion droplets (stabilized either by 0.3% soy lecithin (SL) or 0.1% whey protein isolate (WPI), and 4.5% protein (either WPI or whey protein aggregates (WPA). In the presence of polysaccharide, systems containing SL-stabilized emulsion droplets (SE) and WPI showed a high degree of aggregation and coalescence, whereas systems containing WPI-stabilized emulsion droplets (WE) and WPA were less sensitive to such phenomena. Aggregation or micro-phase separation was especially observed for mixtures containing xanthan, which led to a heterogenous structure, and thus higher friction coefficients. A more homogeneous structure without aggregation was mostly observed for mixtures with guar gum, and provided lower friction coefficients, i.e. better lubrication. The rheological and tribological properties in different sliding regimes were correlated with sensory perception. Systems with a relatively low degree of shear-thinning (i.e. viscosity showed low dependency of shear rate) and low friction coefficients (0.1–0.25, at 10–100 mm/s) gave higher values for the attributes creamy, thick, and fatty. This was mostly observed for homogeneous structures. The attributes slippery, dry and mouthcoating showed strong correlations with friction coefficients (at 10–50 mm/s) and the slope of frictional curves (at 0.1–10 and 30–470 mm/s). These results can be used to optimize the physical and sensory properties of such mixed systems. Graphical abstract: Image 1 Highlights: Adding polysaccharides in dairy beverages affected microstructure of the mixture. Aggregation and micro-phase separation increase friction coefficients. Among the used polysaccharides guar gum promoted lubrication most efficiently. Sensory perception could be linked to frictional behavior at various sliding speeds. Changes in friction coefficients with speed were linked to perception.